Happily ever after a semiotic and content analysis of Walt Disney animated feature films - Banatao, Rheah Leizl R.; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The general objective of this study is to find out the denotative and connotative meanings of the signs in Walt Disney animated feature films as well as the values shown in these films. Eight films were studied starting from The Little Mermaid, which was released in 1990 to Mulan, which was released in 1998. This research is descriptive in nature using quantitative and qualitative analysis. The first phase of the study used content analysis in order to describe the similarities and differences in the content of the animated films. To facilitate this phase a content analysis coding frame was used. In order to further study the manifest and latent meanings of the images seen in these films, a semiotic approach was used fir he second phase of the study. Results showed that there have been an equal number of male and female heroes. They are shown as progressive characters who begin by being commoners in a community to becoming saviors and overcomers of evil. They display positive attitudinal traits of kindness, perseverance and bravery as well as negative attitudinal traits such as curiosity. Almost all were portrayed as young, attractive and able to perform the tasks set out for them. On the other hand, the villains were drawn in dark colors, bringing to mind the stereotype that dark is associated with evil while light is associated with good. They are portrayed as aggressive and secretly bent on plotting the downfall of the heroes. They are also people of high position, possessing positive attitudinal traits such as decisiveness and negative attitudinal traits that outnumber the positive ones, such as unkindness, aggressiveness and selfishness. Present in these films were secondary characters who are on the side of either the hero or the villain. They help in the primary characters in attaining their goals while providing the element of comedy, parental authority or romantic love in the films. Significant objects surrounded the characters that aided them in attaining their goals. Some were used for spying such as crystal balls and mirrors, in order to be one step ahead of the enemy. Others, though not inherently evil, were used to hurt the enemy -- weapons such as thunderbolts, guns and spears. Others still were just used to identify the characters, such as crown for royalty and flag for the nation the character belongs. All eight films had all three conflicts (social, physical and psychological) present in them. The most obvious being the conflict between good and evil, in which the hero (on the side of good) always triumphs over the villain (on the side of evil). Also present is the conflict between parent and child in which the parents asserts his authority over the child and the child rebels. Most of the conflicts were resolved through forgiveness of the hero where he may have made a mistake or forgiveness of the hero by the authority (such as parents) whom he has displeased. Also the conflicts were resolved by death, that is, death of the villains. All of the films ended happily. The most predominant theme among the Disney movies is that of love followed by power. Positive as well as negative values can be seen in Disney's animated films. Present in all films is the positive value of self-sacrifice or that of giving one's life for another. The next predominant value is that of family love, considering that almost all of the characters have family ties. And along with family love is group commitment, that is support and accountability within the group.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Walt Disney characters; Film criticism